Inside out: Relations between the microbiome, nutrition, and eye health. (November 2022) - Grant, Maria B.; Bernstein, Paul S.; Boesze-Battaglia, Kathleen; Chew, Emily; Curcio, Christine A.; Kenney, M. Cristina; Klaver, Caroline; Philp, Nancy J.; Rowan, Sheldon; Sparrow, Janet; Spaide, Richard F.; Taylor, Allen
Abstract: Age-related macular degeneration (AMD) is a complex disease with increasing numbers of individuals being afflicted and treatment modalities limited. There are strong interactions between diet, age, the metabolome, and gut microbiota, and all of these have roles in the pathogenesis of AMD. Communication axes exist between the gut microbiota and the eye, therefore, knowing how the microbiota influences the host metabolism during aging could guide a better understanding of AMD pathogenesis. While considerable experimental evidence exists for a diet-gut–eye axis from murine models of human ocular diseases, human diet-microbiome-metabolome studies are needed to elucidate changes in the gut microbiome at the taxonomic and functional levels that are functionally related to ocular pathology. Such studies will reveal new ways to diminish risk for progression of- or incidence of- AMD. Current data suggest that consuming diets rich in dark fish, fruits, vegetables, and low in glycemic index are most retina-healthful during aging. Highlights: The etiology of AMD is multifactorial including nutritional factors, genetic variants mainly in the complement pathway, environmental risk factors, and the intestinal microbiome. Nutritional risks for AMD are as great as the risk imposed by smoking. Defining interactions between nutrition, metabolomes, microbiomes, physiological responses, and clinical ophthalmologic data represent an "interactome" network that may help identify novel biomarkers of AMD progression. Clinical studies using plasma metabolites (lipids, advanced glycation end products, lutein, markers of barrier dysfunction) and inflammatory molecules will help elucidate interactions between the gut microbiome and AMD.